Inhibition but not activation of neuronal P2X7 receptors plays roles in brain injury after optic nerve transaction and focal cerebral ischemia - Çağlayan, Ahmet Burak; Beker, Mustafa Çağlar; Kılıç, Ülkan; Keleştemur, Taha; Çağlayan, Berrak; Kılıç, Ertuğrul (Springer Heidelberg, 2014)
[Abstract Not Available]
Journal of Neurology
Keywords: P2X7; Brain Injury; Optic Nerve Transaction; Focal Cerebral Ischemia